2020
DOI: 10.1177/1369433220944506
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance test of rammed earth wall with different structural columns

Abstract: Rammed earth wall load-bearing dwellings are widely distributed in western China. Rammed earth has the advantages of warm in winter and cool in summer, and it is a kind of sustainable construction material. In recent years, in previous earthquakes, the collapse of rammed earth buildings is serious, resulting in huge losses of personnel and property. To improve the seismic performance of rammed earth buildings and retain the characteristics of local buildings, a reinforcement measure with additional structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…In order to study failure mode of CEB wall under earthquake, a two-story newly built adobe demonstration house in northwestern Shaanxi Province, China, was selected as the prototype. The size of the prototype was 4000 mm × 2400 mm × 480 mm, and the 1/2 scale was adopted to obtain the size of the adobe wall used in this experiment is 2000 mm × 1200 mm × 240 mm (El-Nabouch et al, 2017;Zhou et al, 2020). The rotary brick pressing mechanism was adopted to make CEBs, and 6 pieces of the walls were built with different types of CEBs including the hollow CEB, the hollow CEB with core column and the solid CEB.…”
Section: Test Specimensmentioning
confidence: 99%
“…In order to study failure mode of CEB wall under earthquake, a two-story newly built adobe demonstration house in northwestern Shaanxi Province, China, was selected as the prototype. The size of the prototype was 4000 mm × 2400 mm × 480 mm, and the 1/2 scale was adopted to obtain the size of the adobe wall used in this experiment is 2000 mm × 1200 mm × 240 mm (El-Nabouch et al, 2017;Zhou et al, 2020). The rotary brick pressing mechanism was adopted to make CEBs, and 6 pieces of the walls were built with different types of CEBs including the hollow CEB, the hollow CEB with core column and the solid CEB.…”
Section: Test Specimensmentioning
confidence: 99%
“…Strength and durability of rammed earth construction can be improved to a great extent by using ordinary Portland cement (OPC) as stabilizer varying from 4% to 12%. Stabilized rammed earth constructions were superior in terms of strength and durability when compared to unstabilized rammed earth construction (Arslan et al, 2017;Bahar et al, 2004;Hejazi et al, 2012;Jayasinghe and Kamaladasa, 2007;Raavi and Tripura, 2020;Tripura and Singh, 2015;Walker, 1995;Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the investigation and analysis of the earthquake damage mechanism of raw-soil buildings, Pavan et al [6] analyzed the interfacial behavior of cement-stabilized rammed Earth. Zhou et al [7] conducted a shaking table test and analyzed the scale model of two types of adobe house reinforcement modes. e results showed that the proposed plaster-adobewall structure and the wooden-frame-adobe-wall structure could resist earthquakes of magnitude 8.0.…”
Section: Introductionmentioning
confidence: 99%